2015
DOI: 10.1016/j.colsurfa.2015.05.048
|View full text |Cite
|
Sign up to set email alerts
|

The kinetics of gold(III) extraction by pyridine-2-azo‑p‑dimethylaniline in water and in micellar systems

Abstract: The kinetics of reaction between AuCl4-, and the azo-dye pyridine-2-azo-pdimethylaniline (PADA) have been investigated in water and in the presence of DTAC micelles, using classical spectrophotometry and the stopped-flow technique. PADA reacts with different chloro/hydroxo gold(III) complexes, in turn formed as the pH and Cl-concentration were changed, according to a network of parallel paths. In aqueous solution, at low pH values, a fast step is observed which is ascribed to the ligand induced expulsion of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 18 publications
0
8
1
Order By: Relevance
“…The extent of retention is independent of the solution pH. [8], is totally different from the spectrum in water. In contrast, the shape of the spectrum in SDS does not differ from that of the spectrum recorded in water.…”
Section: The Partitioning Of Pada Au(iii) and Au-pada Complex Betweementioning
confidence: 79%
See 2 more Smart Citations
“…The extent of retention is independent of the solution pH. [8], is totally different from the spectrum in water. In contrast, the shape of the spectrum in SDS does not differ from that of the spectrum recorded in water.…”
Section: The Partitioning Of Pada Au(iii) and Au-pada Complex Betweementioning
confidence: 79%
“…The commercially available ligand PADA ( Figure 1) is totally adsorbed on a variety of surfactants, including SDS [4] and has proven to be an excellent metal extractor, being able to transfer metal ions from water to micellar phases with yields approaching 100% [5][6][7] Moreover, we have found that PADA is able to complex Au(III) with great affinity even if the coordination shell of the metal is occupied, as in AuCl4 - [8,9]. In this case, a molecule of PADA replaces two chloride ions forming a strong chelate.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Note that Au(III) absorbs in the UV [31], hence, the UV-vis spectrophotometric technique could have been used to quantify the gold content. However, spectrophotometry becomes unsuitable for low Au(III) concentrations ( = 7.1 × 10 3 M −1 cm −1 at 233 nm).…”
Section: Instrumentation and Methodsmentioning
confidence: 99%
“…Thus, under such conditions, the rate of hydrolysis is negligible compared with rate of piperidinolysis of PSa -. It is widely known that the ability of surfactant to form nanoparticle aggregates such as micelles could create different media in reaction phases that might affect the rate of the reactions [39,40]. A pseudophase micellar (PM) model can be used to explain the effect of TTABr micelles on the rate of nucleophilic reaction between Pip and PSa - [41] as 4) and (5) with kinetic parameters (k 0 , h, K X/S and k 0 , X k cat , K X/S ) listed in Table 1, at ½4-FBzNa] op 0 ¼ 0:0046 (filled circle), 0.0093 (filled triangle) and 0.0131 (filled diamond) 4) and (5) with kinetic parameters (k 0 , h, K X/S and k 0 , X k cat , K X/S ) listed in Table 1 [26].…”
Section: Kinetic Measurementsmentioning
confidence: 99%